2017
DOI: 10.1111/trf.14204
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of hepatitis C virus RNA in blood donors with anti‐hepatitis C virus reactivity in Rwanda

Abstract: The prevalence of anti-HCV among Rwandan blood donors has probably been overestimated previously due to the high rate of nonconfirmable anti-HCV reactivity. Further study of the involved mechanism is needed to avoid loss of blood products and distress for blood donors and other test recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…The results of the viraemic rate were 55.66% for the people tested within the timeframe of the study. This is comparable with a study of 324 patients selected from non-HCV-related laboratory referrals conducted at a tertiary Rwandan hospital that estimated a viraemic rate of 59.62%20 and a study conducted among blood donors in Rwanda that reported a viraemic rate of 56% 11. Studies in Uganda,21 Kenya22 and Malawi23 have also found low viraemic rates among individuals who screen positive for anti-HCV.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The results of the viraemic rate were 55.66% for the people tested within the timeframe of the study. This is comparable with a study of 324 patients selected from non-HCV-related laboratory referrals conducted at a tertiary Rwandan hospital that estimated a viraemic rate of 59.62%20 and a study conducted among blood donors in Rwanda that reported a viraemic rate of 56% 11. Studies in Uganda,21 Kenya22 and Malawi23 have also found low viraemic rates among individuals who screen positive for anti-HCV.…”
Section: Discussionsupporting
confidence: 75%
“…Studies in Uganda,21 Kenya22 and Malawi23 have also found low viraemic rates among individuals who screen positive for anti-HCV. One hypothesis for these findings is high rates of false positives for anti-HCV due to cross-reactivity with immunoglobulins from other parasitic diseases such as schistosomiases 11 21 22 24. Globally, studies have shown considerable variation in viraemic rates with a range of 9%–100% and average of about 66%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one review of publications from 1994 to 2010 addressing this issue, only 50% and 20% of samples initially reactive for HIV and HCV, respectively, were found to be positive on confirmatory tests . More recently, a study of Rwandan blood donors found that only 40 of 120 samples found to be reactive by the regular blood centre testing were found to have positive or intermediate results on confirmatory testing . Thus, the absence of confirmatory testing is likely a source of unnecessary donor loss (and donor distress with possible ripple effects to other potential donors) in SSA.…”
Section: Transfusion‐transmissible Infections (Tti)mentioning
confidence: 99%
“…Blood transfusion is the major cause of hepatitis B and Confections in many parts of the world especially in developing countries where the screening system is A B S T R A C T not much established. In Scandinavia, the prevalence of hepatitis in transfusion recipients was 0% (Edgren et al, 2018) and in Rwandait was 1.6% (Twagirumugabe et al, 2017). Patients with β-thalassemia, hemophilia and uremia, who receive multiple blood transfusions, are at an increased risk of transfusion related diseases (Tafesse et al, 2017).…”
mentioning
confidence: 99%